(untitled) (Transactions of the Association of European Schools of Planning, 2020)
Neoliberal urban restructuring constitutes an underlying challenge facing cities and communities around the world. Public space, as a medium of political engagement and social interactions, may represent a vehicle for resistance against patterns of shrinking democracy. In its capacity as a place for active democracy, public spaces – the lived spaces of contemporary societies – deserve greater care, attention, and critical reflection. As movements evolve to confront new challenges, explore new opportunities, negotiate with new actors and circumstances, and utilise new technologies and platforms, our understanding of the agency of democracy – supported through an understanding of civic dignity – must also advance. This paper aims at examining the role of public space in reclaiming and reinstating democracy. By drawing on empirical findings from cities worldwide, explored through the lens of multiple disciplines, it argues that the study of urban protest might show directions for a new, dignified politics of public space. It asks how this study may enable planners and designers to contribute to the spatial emergence of human and civic dignity.